2015
DOI: 10.1016/j.lfs.2015.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal zinc prevents communication impairments and BDNF disturbance in a rat model of autism induced by prenatal lipopolysaccharide exposure

Abstract: Aims: Previous investigations by our group have shown that prenatal exposure to lipopolysaccharide (LPS),which mimics infections by Gram-negative bacteria, induced autistic-like behavior. No effective treatment yet exists for autism. Therefore, we used our rat model to test a possible treatment for autism.We selected zinc as the prenatal treatment to prevent or ease the impairments induced by LPS because LPS induces hypozincaemia.Materials and methods:We evaluated the effects of LPS and zinc on female reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 70 publications
2
36
0
3
Order By: Relevance
“…Because the brain contains a dynamic pool of labile zinc, which is stored in synaptic vesicles through the action of ZnT3 (SLC30A3) and released upon depolarization to modulate synaptic physiology, it has been proposed that abnormalities in synaptic zinc levels may contribute to the above-mentioned brain dysfunctions such as microcephaly that are observed in nutritionally zinc-deficient animals33. Consistent with these ideas, dietary supplementation or injections of zinc have been shown to have beneficial effects in ASD patients34353637.…”
Section: Discussionmentioning
confidence: 99%
“…Because the brain contains a dynamic pool of labile zinc, which is stored in synaptic vesicles through the action of ZnT3 (SLC30A3) and released upon depolarization to modulate synaptic physiology, it has been proposed that abnormalities in synaptic zinc levels may contribute to the above-mentioned brain dysfunctions such as microcephaly that are observed in nutritionally zinc-deficient animals33. Consistent with these ideas, dietary supplementation or injections of zinc have been shown to have beneficial effects in ASD patients34353637.…”
Section: Discussionmentioning
confidence: 99%
“…The AST treatment was given for 6 weeks; from postnatal day 91 to 132 with the intent to reduce the stress level that was enhanced by prenatal LPS exposure in our mice model. This timing of AST treatment was rationally decided after reviewing the previous studies demonstrating neurochemical abnormalities in the adults after prenatal LPS administration [ 72 74 ]. In control_AST group, only astaxanthin was given to the animals that were not prenatally LPS-exposed for better comparison and to understand the effect of AST on prenatally LPS-exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that no differences in the number and total vocalization, and mean and maximum call duration were detected in the 11‐day‐old offspring of Wistar rats that received LPS (100 μg/kg) on gestational day 9.5, when they were tested for 40‐kHz USVs in the maternal‐isolation paradigm . The results discussed above are summarized in Table .…”
Section: Maternal Immune Activation and Ultrasonic Vocalizations In Ratsmentioning
confidence: 93%